2013
DOI: 10.1021/je300819g
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium for Mixtures of Ethylethylenediamine, Ethylenediamine, and Water

Abstract: The temperature and the composition of the vapor and liquid phases at equilibrium were measured at atmospheric pressure and (50 and 20) kPa for the binary mixtures: water (1) and ethylenediamine (2, EDA); water and ethylethylenediamine (3, EtEDA); and EDA and EtEDA. For the ternary mixture of water, EDA, and EtEDA, equilibrium conditions were measured at atmospheric pressure. The vapor pressure of EtEDA was measured in the temperature range from (358 to 402) K, and Antoine parameters were fitted to the data. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The ethylenediamine-water mixture has an azeotrope with a maximum separation point of 0.55 (molar fraction), so the fractional distillation proposed for TRAB could not be used for a TRENB [27][28][29]. Therefore, other separation methods, such as an azeotropic distillation or pressure swing distillation would need to be used to separate ethylenediamine and water using waste heat.…”
Section: Recharging the Electrolytesmentioning
confidence: 99%
“…The ethylenediamine-water mixture has an azeotrope with a maximum separation point of 0.55 (molar fraction), so the fractional distillation proposed for TRAB could not be used for a TRENB [27][28][29]. Therefore, other separation methods, such as an azeotropic distillation or pressure swing distillation would need to be used to separate ethylenediamine and water using waste heat.…”
Section: Recharging the Electrolytesmentioning
confidence: 99%
“…One of these factors that could potentially raise concern when running the process long-term on a large scale is the high vapor pressure of EDA. The vapor pressure of a pure EDA solution at 20 °C is 1.3 kPa, which is comparable with that of water (2.3 kPa) at the same temperature . This negatively affects the process performance by reducing the absorbent CO 2 capacity and increasing the energetics, since EDA vapor would leave the system through the absorbent gas phase effluent over time.…”
Section: Introductionmentioning
confidence: 98%
“…The vapor pressure of a pure EDA solution at 20 °C is 1.3 kPa, which is comparable with that of water (2.3 kPa) at the same temperature. 22 This negatively affects the process performance by reducing the absorbent CO 2 capacity and increasing the energetics, since EDA vapor would leave the system through the absorbent gas phase effluent over time. In this study, we investigated the possibility of using a mixture of EDA and another amine with a lower vapor pressure to reduce the absorbent vapor pressure, minimizing absorbent loss.…”
Section: Introductionmentioning
confidence: 99%
“…The VLE of EDA–water was satisfactorily modeled by universal quasichemical (UNIQUAC) 11 equation at various pressures. 12 The VLE of binary mixtures of several diamines with water was correctly modeled by the method of Barker which is based on the excess Gibbs function. 13 Regarding binary mixtures of EDA with alcohols, Kato et al 14 reported the experimental VLE data for EDA and dipropylamine with methanol, ethanol, and 2-propanol; the VLE data were correlated by Wilson 15 equation.…”
Section: Introductionmentioning
confidence: 99%